PENTINGNYA PENGELOLAAN KELAS YANG POSITIF DALAM PEMBELAJARAN PAI DI SDIT BAITUL ILMI TAMBUN UTARA BEKASI - Ayu Solihah; Aisyah Nur Afiifah; Fadilla Ilmi Qur’ani; Dimas Ilham Arrobi; Ami Latifah (UNISAN JURNAL, 2023)
This exploration means to figure out how homeroom the executives is carried out in PAI learning at SDIT Baitul Ilmi Tambun Utara Bekasi. Furthermore, what are the supporting and restraining factors for executing the homeroom the executives model in PAI learning at Riyadlul Arkham Tembong Plinlahan Pandaan Primary School. This exploration is subjective examination, occurring at SDIT Baitul Ilmi Tambun Utara Bekasi. The exploration subjects were PAI instructors and understudies at SDIT Baitul Ilmi Tambun Utara Bekasi. Information assortment was completed utilizing perception, meetings and documentation strategies. The information examination utilized is information assortment, information decrease, information show, making determinations. The overall finish of this exploration shows that PAI instructors’ getting the hang of arranging starts with the making of learning apparatuses comprising of: instructive schedule, powerful time examination, prospectus, yearly program, semester program, RPP, KKM/KBM, day to day plan and evaluation design. Second, the execution of PAI learning is affected by the learning techniques utilized by PAI instructors. The learning media utilized by instructors who educate with KTSP and the 2013 Educational program are as yet straightforward and manual, for example, utilizing idea maps, pictures, cardboard with Al-Qur’an or Hadith refrains composed on them, and not yet utilizing science and innovation based. . media. PAI educators give adjustment training in the homeroom and outside the study hall. The Islamic Strict Training learning director at SDIT Baitul Ilmi, North Tambun subdistrict, Bekasi Rule does Islamic Strict Schooling learning the board as per the educational program. PAI educators get ready learning plans, do learning, complete assessments, do PAI MGMP in taking care of learning the board issues.